Epidemiologic, clinical and laboratory features of scrub typhus in thirty Thai children - Sirisanthana V. (2014)
Background. Scrub typhus, a potentially fatal rickettsial infection, is common in Asia. Although serologic surveys suggested that as many as one-fourth of cases of scrub typhus might be in children, very few reports of childhood scrub typhus are available in the medical literature. Objectives. To document the clinical, laboratory and epidemiologic characteristics of pediatric patients with scrub typhus. Methods. From January 1, 2000 to December 31, 2001, all pediatric patients at Chiang Mai University Hospital who had obscure fever for >5 days were tested for indirect immunofluorescent antibody (IFA) against Orientia tsutsugamushi, the causative organism of scrub typhus. Scrub typhus was diagnosed on the basis of either a single IFA titer against O. tsutsugamushi ≥1/400 or a 4-fold or greater rise in IFA titer to at least 1/200. Results. Thirty children with scrub typhus were enrolled. Most were diagnosed during the rainy months of June to November. Common physical signs included lymphadenopathy (93%), hepatomegaly (73%), eschar (68%), conjunctival hyperemia (33%), maculopapular rash (30%) and splenomegaly (23%). Eleven patients had interstitial pneumonitis and 1 patient had meningitis. All patients responded well to doxycycline or chloramphenicol. The average interval to defervescence after treatment was 29 h (range, 6 to 72). Conclusions. Clinical and epidemiologic features of 30 pediatric patients with scrub typhus are reported in a prospective study. The presence of eschar was helpful in making the diagnosis. Complications included pneumonitis and meningitis. All cases responded well to treatment with antibiotic.